Magnetic nanohydrogel obtained by miniemulsion polymerization of poly (acrylic acid) grafted onto derivatized dextran - Piazza, Rodolfo Debone [UNESP] (2017)
This study describes the synthesis of magnetic nanohydrogels by miniemulsion polymerization technique. Dextran was derivatized by the glycidyl methacrylate to anchor vinyl groups on polysaccharides backbone, allowing its use as a macromonomer for miniemulsion polymerization, as confirmed by proton nuclear magnetic resonance spectroscopy (C-13 NMR). Magnetite nanoparticles were synthesized by coprecipitation, followed by air oxidation to maghemite. The results of X-ray diffractometry (XRD), Raman and transmission electron microscopy (TEM) analysis showed that maghemite nanoparticles were obtained with a diameter of 5.27 nm. The entrapment of iron oxide nanoparticles in a dextran nanohydrogel matrix was confirmed by thermogravimetric analysis (TGA), scanning transmission electron microscopy (STEM) and Zeta potential data. The magnetic nanohydrogels presented superparamagnetic behavior and were colloidal stable in physiological during 30 days. Our findings suggest that the synthesized magnetic nanohydrogel are potential candidates for use in drug delivery systems due to its physicochemical and magnetic properties.